Introduction: Speculative Finance/Speculative Fiction. - Higgins, David M.; O'Connell, Hugh C. (CR: The New Centennial Review)
The article examines how the historical rise of dominant finance capital gives form to speculative fiction. Topics covered include William Gibson's 2003 novel "Pattern Recognition," an essay about the speculative in science fiction by Arjun Appadurai, and a reexamination of the tradition of critical realism by Michael Löwy.